Stromal interaction molecule 1 and its role in the regulation, proliferation and protein expression in follicular ML-1 thyroid cancer cells - Butt, Basit Iqbal (fi=Turun yliopisto|en=University of Turku|, 2015)
Calcium (Ca2+) is involved in the regulation of variety of cellular functions including hallmarks of cancer development such as cellular migration and cellular proliferation. Store-operated calcium entry (SOCE) is a central mechanism in cellular calcium signaling and in maintaining the cellular calcium balance. Stromal interaction molecule 1(STIM1) has been identified as an important constituent of SOCE. In this thesis , the STIM1 proteins are studied for their importance in cellular processes and their effects on the expression of S1P1, S1P2, S1P3, VEGFR-2, and TRPC-1 in follicular ML-1 thyroid cancer cells. The results show the importance of STIM1 proteins in SOCE in these cells. The SOCE is significantly reduced in the STIM1 knockdown cells. The results also show the importance of STIM1 proteins in the expression of S1P2 and VEGFR-2 in these cells, as knockdown of STIM1 was shown to upregulate the expression of S1P2 and VEGFR-2. The migration and proliferation is also considerably reduced in the cells in which STIM1 has been knocked down showing the significance of STIM1 in the migration and proliferation in these cells.